Linear and Non-Linear Optical Properties for Organic Semiconductor (CuPc) Thin Films - Mohammed, Reem Rafea; Hussein, Mohammed T. (Iraqi Journal of Physics, 2021)
Thin films of CuPc of various thicknesses (150,300 and 450) nm have been deposited using pulsed laser deposition technique at room temperature. The study showed that the spectra of the optical absorption of the thin films of the CuPc are two bands of absorption one in the visible region at about 635 nm, referred to as Q-band, and the second in ultra-violet region where B-band is located at 330 nm. CuPc thin films were found to have direct band gap with values around (1.81 and 3.14 (eV respectively. The vibrational studies were carried out using Fourier transform infrared spectroscopy (FT-IR). Finally, From open and closed aperture Z-scan data non-linear absorption coefficient and non-linear refractive index have been calculated respectively using He-Ne laser which have beam waist of (24.2 μm), wave-length of (632.8 nm) and Rayleigh thickness was 2.9 mm.